Demographic and socio-cultural aspects of burns patients admitted in a tertiary care centre - Nair, C. K. Velayuthan; Gopinath, Vinu; Ashok, Vishnu G. (International Surgery Journal, 2017)
Background: Burn injury is a serious pathology, potentially leading to severe morbidity and significant mortality, but it also has a considerable health-economic impact. Burn injuries rank among the most severe types of injuries suffered by the human body with an attendant high mortality and morbidity rate. The objective of this study was to identify the demographic and socio-cultural aspects of burn patients attending a tertiary care centre. Methods: A cross sectional study was carried out in the burns unit of a tertiary care centre. All burns cases admitted to the burns unit for the period of one year were included. Results: Out of the 150 burns patient’s majority were females belonging to the age group 21 to 30 years. 80% of the burn injuries occurred at home. Cooking was the main factor for burns in domestic set up. Flames represented the common agent of burn injuries. Conclusions: The current study gives important information about sociocultural factors involved in burn injuries which in turn will help in identifying the high-risk population for preventing future burn injuries.